Influence of biochar and compost on phytoremediation of oil-contaminated soil. Issue 1 (2nd January 2018) - Saum, Lindsey; Jiménez, Macario Bacilio; Crowley, David
ABSTRACT: The use of pyrolyzed carbon, biochar, as a soil amendment is of potential interest for improving phytoremediation of soil that has been contaminated by petroleum hydrocarbons. To examine this question, the research reported here compared the effects of biochar, plants (mesquite tree seedlings), compost and combinations of these treatments on the rate of biodegradation of oil in a contaminated soil and the population size of oil-degrading bacteria. The presence of mesquite plants significantly enhanced oil degradation in all treatments except when biochar was used as the sole amendment without compost. The greatest extent of oil degradation was achieved in soil planted with mesquite and amended with compost (44% of the light hydrocarbon fraction). Most probable number assays showed that biochar generally reduced the population size of the oil-degrading community. The results of this study suggest that biochar addition to petroleum-contaminated soils does not improve the rate of bioremediation. In contrast, the use of plants and compost additions to soil are confirmed as important bioremediation technologies.